Expert System for Jeans Product Recomendation using Forward Chaining based on Laravel - Goldie Gunadi; Serlianti Waruwu (Jurnal Manajemen Informatika, Sistem Informasi dan Teknologi Komputer (JUMISTIK), 2026)
Selecting jeans products that match user preferences is often challenging due to the wide variety of models and styles available. This study aims to develop a web-based expert system for recommending jeans products using the forward chaining method. The inference process is carried out based on facts provided by users through a series of questions and processed using rule-based knowledge to determine the appropriate jeans category. The system was developed using the Laravel framework and applies a filtering mechanism based on attributes such as color, price, age, height, event type, and outfit type to improve the relevance of recommendations. System testing was conducted using black box testing and accuracy testing by comparing system results with expert results. The testing results show that all system functions run properly and the accuracy level reached 100% based on the test data used. Therefore, the developed system is able to assist users in selecting jeans products more effectively and efficiently.